ADVANCED METHODS AND PROCEDURES FOR DISCOVERING COVERT CHANNELS, CAVITIES AND PIPELINES WITH VIBRO-ACOUSTIC TECHNIQUE - Sergey O. Gaponenko; Alexander E. Kondratiev (Вестник Северо-Кавказского федерального университета)
There is an urgent need for developing newer methods and techniques for discovering hidden channels, cavities and pipes, of which the most promising, according to the authors, is the acoustic method using resonance. To implement the method proposed there has been designed and manufactured a specific measurement and diagnostics set of equipment to locate hidden pipelines employing respective software.